Cross-cultural poetics in Kateb, Salih, Djebar and Dib - Clark, C (2013)
The present study elaborates a poetics of cross-cultural writing. Its primary theoretical reference is the ‘cross-cultural poetics’ (poétique de la relation) of Edouard Glissant: a set of poetic tropes and narrative structural strategies that he identifies in the mixed cultural setting of the Caribbean, in Le Discours antillais. My thesis argues that if these poetic strategies are indeed a response to specific social, cultural and political situations, then if analogous situations were considered elsewhere, we might expect an analogous poetics to arise. Taking North Africa as an example context, and specifically the novels of the Algerians Kateb Yacine, Assia Djebar, Mohammed Dib, and the Sudanese Tayeb Salih, I argue that these writers’ complex poetic strategies engage with – indeed, help to articulate – analogous socio-political concerns arising in their homelands. The formal poetical analysis of these authors is based on several key thematic tropes and structural strategies that Glissant advocates in his cross-cultural poetics. My five chapters consider roots and origins, living landscapes, silence and screams, literary opacity, and structural polyphony. They also develop a new critical vocabulary to describe how Glissant’s poetical strategies might take form at a close textual level; my analysis reveals a complex, and reciprocal, relationship between poetic expression and socio-political context. Glissant’s work is therefore shown to be more broadly relevant, but the founding tenets of his theory are also interrogated and questioned; the comparison with a North African setting entails a (re)assessment of the underlying conceptions of Glissant’s poetics – of the implicit logic by which he connects poetic form to social, cultural and political factors. These factors, for Glissant, also display a clear overlap with the (post)colonial; in studying cross-culturality, the postcolonial, and the poetics engendered by their overlapping, my thesis presents a specific critical focus for the postcolonial literary field.